2006
DOI: 10.1021/nl052405t
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Labeled Near-Infrared Quantum Dots for Imaging Tumor Vasculature in Living Subjects

Abstract: We report the in vivo targeting and imaging of tumor vasculature using arginine-glycine-aspartic acid (RGD) peptide-labeled quantum dots (QDs). Athymic nude mice bearing subcutaneous U87MG human glioblastoma tumors were administered QD705-RGD intravenously. The tumor fluorescence intensity reached maximum at 6 h postinjection with good contrast. The results reported here open up new perspectives for integrin-targeted near-infrared optical imaging and may aid in cancer detection and management including imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
788
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(810 citation statements)
references
References 37 publications
19
788
1
2
Order By: Relevance
“…Due to their super brightness and photostability, quantum dots have sparkled tremendous interests in the biological sciences community and have rapidly found its way into many applications including in vivo animal imaging [17,18]. Even with their superior optical properties of QDs, the same challenges remain for optical imaging at non-superficial tissue sites, which are the presence of strong background autofluorescence and photon absorbance/ scattering by living tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their super brightness and photostability, quantum dots have sparkled tremendous interests in the biological sciences community and have rapidly found its way into many applications including in vivo animal imaging [17,18]. Even with their superior optical properties of QDs, the same challenges remain for optical imaging at non-superficial tissue sites, which are the presence of strong background autofluorescence and photon absorbance/ scattering by living tissue.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[29][30][31] Nonspecific binding in tumors could nevertheless be caused either by nonspecific adsorption of the RGD peptide or by the qdot surface to tumor neovasculature. To control for this, similar peptide RAD was employed on qdots.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…This makes them highly conducive to preclinical optical imaging. [1][2][3][4][5][6][7][8] Qdots have been used in living subjects to target tissue-specific vascular biomarkers 3 and cancer cells 1,2,4,5,8 and to identify sentinel lymph nodes in cancer 9-12 with the potential for © Copyright 2008 by the American Chemical Society * Corresponding author: mail, Sanjiv S. Gambhir, MD, PhD, Director, Molecular Imaging Program at Stanford (MIPS), Head, Division of Nuclear Medicine, Professor, Department of Radiology and Bio-X Program, The James H. Clark Center, 318 Campus Dr., East Wing, first Floor, Stanford, CA 94305-5427; phone, 650-725-2309; fax, 650-724-4948; sgambhir@stanford.edu. Supporting Information Available: Videos showing RGD-qdot injection and binding, RGD-qdots in normal mouse vasculature and tumor vasculature, Cy5.5-RGD block of RGD-qdots in tumor, unconjugated qdots entering the tumor vasculature, and Cy5.5 and Cy5.5-RGD leaking out of the tumor neovasculature and descriptions of nanoparticle conjugates, the tumor model, intravital microscopy, statistics, electron microscopy, and U87MG cells incubated with RGD-qdots.…”
mentioning
confidence: 99%
“…After 24 h of probe injection, the images of the tumors are further reduced and the intensity of fluorescence is decreased. This might be due to the gradual degradation of ligands and coating layer on the surface of probe by lysosomal enzymes (18,32,33), leading to gradual decreases of the probe binding ability and gradual quenching of the fluorescent quantum dots. Our previous studies (10) have also shown that in vivo imaging can detect a minimum of 10 4 cancer cells labeled with NIRF-QDs in the presence of skin barrier, which was 100-fold higher than the minimal detection limit of CT and MRI.…”
Section: Discussionmentioning
confidence: 99%